2015
DOI: 10.3389/fpls.2015.00409
|View full text |Cite
|
Sign up to set email alerts
|

The knottin-like Blufensin family regulates genes involved in nuclear import and the secretory pathway in barley-powdery mildew interactions

Abstract: Plants have evolved complex regulatory mechanisms to control a multi-layered defense response to microbial attack. Both temporal and spatial gene expression are tightly regulated in response to pathogen ingress, modulating both positive and negative control of defense. BLUFENSINs, small knottin-like peptides in barley, wheat, and rice, are highly induced by attack from fungal pathogens, in particular, the obligate biotrophic fungus, Blumeria graminis f. sp. hordei (Bgh), causal agent of barley powdery mildew. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 112 publications
(152 reference statements)
2
23
1
Order By: Relevance
“…Mla6 is a major NLR-type resistance gene [28, 29], while Rar3 ( Required for Mla6 resistance 3 ) is an unlinked locus required for Mla6 function. Blufensin1 ( Bln1 ) is an inhibitor of basal defense [28] and silencing of Bln1 results in down-regulation of genes involved in nuclear import and the secretory pathway [30]. The mla6 + bln1 double mutant is susceptible (due to the mla6 deletion) , but the bln1 phenotype is masked in plants that contain the Mla6 R gene.…”
Section: Introductionmentioning
confidence: 99%
“…Mla6 is a major NLR-type resistance gene [28, 29], while Rar3 ( Required for Mla6 resistance 3 ) is an unlinked locus required for Mla6 function. Blufensin1 ( Bln1 ) is an inhibitor of basal defense [28] and silencing of Bln1 results in down-regulation of genes involved in nuclear import and the secretory pathway [30]. The mla6 + bln1 double mutant is susceptible (due to the mla6 deletion) , but the bln1 phenotype is masked in plants that contain the Mla6 R gene.…”
Section: Introductionmentioning
confidence: 99%
“…BLN1, a negative regulator of basal defense (Meng et al 2009; Xu et al 2015), was associated with 2H.68 during penetration, but 1H.07 during haustorial growth, implying control by unlinked host loci during pathogen development.…”
Section: Resultsmentioning
confidence: 99%
“…The other MfSTMIR‐interacting protein that we identified was MtSec61γ, and studies on Sec61γ in plants are rare. One study suggested that Sec61γ plays a negative role in barley innate immunity to Blumeria graminis ( Bgh ) (Xu et al ., ). In yeast, Sss1p/Sec61γ, Sec61p/Sec61α and Sbh1p/Sec61β compose a protein‐conducting channel for secretory and transmembrane proteins.…”
Section: Discussionmentioning
confidence: 97%